MEDIA EXPOSURE AS A MEDIATOR OF THE RELATIONSHIP BETWEEN CULTURAL IDENTITY AND BODY IMAGE SATISFACTION AMONG ADOLESCENTS - Anozie, Emmanuella U; Anomchi, Nnadi Happiness (African Journal of Social and Behavioural Sciences, 2025)
This study investigated media exposure as a mediator of the relationship between cultural identity and body image satisfaction among adolescents. Four (4) hypotheses were postulated. Data were collected through convenience sampling using three hundred (300) participants. Results from the data analysis indicate that cultural identity is strongly and positively related to body image satisfaction, r=.59, p<.01, emphasizing that individuals with a stronger cultural identity are more likely to be satisfied with their body image. This highlights the role cultural identity plays in shaping positive perceptions of one’s body. Also, Cultural identity was found to be a significant predictor of media exposure (β=.14, t (203) =4.02, p<.001), with a CI ranging from .21 to .61. This shows that individuals with higher cultural identity are more likely to have greater media exposure. However, media exposure was found to be negatively correlated with body image satisfaction, r=−.05, p>.05, though this relationship was not statistically significant. The negative direction of this correlation implies that higher media exposure may be associated with lower body image satisfaction. Lastly, it was revealed from the result that Media exposure mediated the relationship between cultural identity and body image satisfaction. However, the mediation effect was negative; indicating that while cultural identity positively influences body image satisfaction, increased media exposure slightly diminishes this positive effect. Cultural identity’s total and direct effects on body image satisfaction remained significant, reinforcing the strong positive relationship between these two variables despite the negative mediation by media exposure.